COMPARATIVE DOUBLE BLIND TRIAL OF CEFROXADINE (CGP-9000) AND CEPHALEXIN IN THE TREATMENT OF SIMPLE ACUTE CYSTITIS - KISHI, HIROICHI (CHEMOTHERAPY, 1980)
The usefulness and safety of Cefroxadine (CGP-9000, CXD), a new orally effective cephalosporin, in the treatment of acute simple cystitis was studied by a double-blind method in comparison with CEX. Experimental subjects were selected in accordance with the standard criteria described in the 2nd issue of DrugEfficacy Evaluation inUTI, viz., patients were from 16 to 70 years women having not less than 10 cells/hpf in urinary leukocyte count and 104/ml in urinary organism. CXD was given orally in a dose of 250mg three times daily and CEX in a dose of 250mg four times daily. To patients receiving CXD was administered an inactive placebo once a day. so that the frequency of administration was unified. The results were evaluated in accordance with the standard criteria for Drug Efficacy Evaluation in UTI. In the global clinical efficacy, remarkably effective rate was 87% and effective rate was 98% with CXD, while CEX showed 78% of remarkably effective rate and 99% of effective rate. In the remarkably effective rate, CXD was shown to be superior as a tendency to CEX at a significant level of 10%. CXD improved symptoms in 97%, normalized pyuria in 88%, and eliminated bacteria from the urine in 97%, while CEX 96%, 86% and 95%, respectively. There was no significant difference in these rates. Phycisians in charge judged that CXD was remarkably effective in 77% and more than effective in 94%, while CEX 73% and 94%, respectively. The usefulness of CXD was judged to be very satisfactory in 74% and satisfactory in 91%, while that of CEX was very satisfactory in 70% and satisfactory in 88%. Adverse side-effects were observed in 2 cases treated with CXD and 4 treated with CEX. Among them, one case discontinued CEX because of general exhaustion. There was no significant difference in incidence of adverse reactions.